The Effect Of Brisk Walking Exercise On Blood Pressure In Elderly Hypertension In The Working Area Of The Gajah Ii Community Health Center - Cherlina Pramushinta; Dewi Hartinah; Muhamad Jauhar (International Journal of Health Engineering and Technology, 2026)
Hypertension is a non-communicable disease that often occurs in the elderly and can cause serious complications if not properly controlled. One non-pharmacological therapy that can be done is brisk walking exercise. This study aims to determine the effect of brisk walking exercise on blood pressure in elderly people with hypertension in the Gajah II Community Health Center work area. The study used a quasi-experimental design with a pretest-posttest approach with a control group. The study sample consisted of 36 respondents who were divided into an intervention group and a control group using a total sampling technique. The intervention group was given brisk walking exercise for 20–30 minutes three times a week for two weeks, while the control group was only given health education. Blood pressure was measured using a digital sphygmomanometer before and after the intervention. Data analysis used a paired sample t-test and an independent sample t-test. The results showed that the average systolic blood pressure in the intervention group decreased from 174.06 mmHg to 128.67 mmHg and diastolic from 101.39 mmHg to 83.11 mmHg. Statistical tests showed a significant effect of brisk walking exercise on reducing blood pressure, with a p-value of 0.001 for systolic and 0.011 for diastolic blood pressure. It was concluded that brisk walking exercise is effective as a non-pharmacological therapy to help control blood pressure in elderly hypertensive patients.